Short-term outcomes after complete mesocolic excision compared with 'conventional' colonic cancer surgery. Issue 5 (18th January 2016) - Bertelsen, C A; Neuenschwander, A U; Jansen, J E; Kirkegaard-Klitbo, A; Tenma, J R; Wilhelmsen, M; Rasmussen, L A; Jepsen, L V; Kristensen, B; Gögenur, I; Bols, B; Ingeholm, P; et al.
Abstract: Background: Complete mesocolic excision (CME) seems to be associated with improved oncological outcomes compared with 'conventional' surgery, but there is a potential for higher morbidity. Methods: Data for patients after elective resection at the four centres in the Capital Region of Denmark (June 2008 to December 2013) were retrieved from the Danish Colorectal Cancer Group database and medical charts. Approval from a Danish ethics committee was not required (retrospective study). Results: Some 529 patients who underwent CME surgery at one centre were compared with 1701 patients undergoing 'conventional' resection at the other three hospitals. Laparoscopic CME was performed in 258 (48·8 per cent) and laparoscopic 'conventional' resection in 1172 (68·9 per cent). More extended right colectomy procedures were done in the CME group (17·4 versus 3·6 per cent). The 90-day mortality rate in the CME group was 6·2 per cent versus 4·9 per cent in the 'conventional' group ( P = 0·219), with a propensity score-adjusted logistic regression odds ratio (OR) of 1·22 (95 per cent c.i. 0·79 to 1·87). Laparoscopic surgery was associated with a lower risk of mortality at 90 days (OR 0·63, 0·42 to 0·95). Intraoperative injury to other organs was more common in CME operations (9·1 per cent versus 3·6 per cent for 'conventional' resection; P < 0·001), including more splenic (3·2 versus 1·2 per cent; P = 0·004) and superior mesenteric vein (1·7 versus 0·2 per cent; P < 0·001) injuries. Rates of sepsis with vasopressor requirement (6·6 versus 3·2 per cent; P = 0·001) and postoperative respiratory failure (8·1 versus 3·4 per cent; P < 0·001) were higher in the CME group. Conclusion: CME is associated with more intraoperative organ injuries and severe non-surgical complications than 'conventional' resection for colonic cancer. Abstract : More operative injuries and postoperative sepsis